Public Communication Strategy in the Protest of Garbage Collector Workers - Susanto , Irwan; Sufyanto, Sufyanto (Indonesian Journal of Cultural and Community Development, 2024)
Background: Public perception is vital for government trust and communication. Specific Background: Protests by waste collectors in Sidoarjo impacted the government's image due to controversial waste management fees. Knowledge Gap: Few studies explore the role of government communication in shaping public perception during local policy protests. Aims: This study analyzes the Sidoarjo Communication Office's efforts to maintain a positive image post-protests. Results: The office's inadequate response, especially its failure to engage protestors, worsened negative media coverage. Novelty: The study underscores the importance of transparent crisis communication. Implications: Local governments must strengthen communication strategies to manage public sentiment and maintain credibility during crises. Highlights : Transparent communication prevents negative public sentiment. Lack of engagement worsens media narratives. Robust strategies are needed to maintain government credibility. Keywords: public perception, crisis communication, waste management, local government, Sidoarjo protests